Answer:
Option C is correct
[tex]y = (x+3)^2+2[/tex]
Step-by-step explanation:
The equation of parabola is given by:
[tex]y = a(x-h)^2+k[/tex]
where, (h, k) is the vertex and a is any constant value.
As per the statement:
From the given graph of parabola:
Vertex = (h, k) = (-3, 2)
Substitute in [1] we have;
[tex]y = a(x+3)^2+2[/tex] .....[2]
Since, the graph of parabola cut at (0, 11)
Substitute this point in [2] we have;
[tex]11= a(0+3)^2+2[/tex]
⇒[tex]11= 9a+2[/tex]
Subtract 2 from both sides we have;
[tex]9= 9a[/tex]
Divide both sides by 9 we have;
a = 1
⇒[tex]y = (x+3)^2+2[/tex]
therefore, the equation of the graph is, [tex]y = (x+3)^2+2[/tex]